Bilateral carpal tunnel syndrome and multiple trigger fingers in a child with mucolipidosis Type III disease - Ahmadreza Afshar (Indian Journal of Plastic Surgery)
This report presents a five-year-old girl with mucolipidosis Type III disease who had bilateral carpal tunnel syndrome and eight trigger fingers. Bilateral open carpal tunnel release was performed. The trigger fingers were treated with A1 and A3 pulleys release and the ulnar slips of the flexor digitorum superficialis tendons were removed.